Butyrylcholinesterase genetic variability in Guarani Amerindians from the Brazilian state of Mato Grosso do Sul - Lupe Furtado; Ricardo L. R. Souza; Luiza T. Tsuneto; Maria Luiza Petzl-Erler; Eleidi A. Chautard-Freire-Maia (Genetics and Molecular Biology, 2006)
Human butyrylcholinesterase (BChE; EC 3.1.1.8) is a polymorphic enzyme coded by the BCHE gene (3q26.1-q26.2) while the CHE2 gene (2q33-q35) determines a still not characterized substance that forms a complex with BChE (C5), being the CHE2 C5+ and CHE2 C5- phenotypes detected in electrophoresis. The present study investigated BCHE and CHE2 variability and the BChE activity of Brazilian Guarani Amerindians from the Kaiowá and Ñandeva sub-groups living in several indigenous territories in the Brazilian state of Mato Grosso do Sul. The frequency of the BCHE exon 2 D70G (A) allele was 0.60% ± 0.35% while that of the BCHE exon 2 G390V (F-2) allele, never before screened in Amerindians, was 8.82% ± 1.35%. This is the first time that the BCHE gene exon 4 A539T (K) allele has been surveyed in Brazilian Amerindians where it was found at a frequency of 3.69% ± 0.85%, similar to that found in Chilean Mapuche Amerindians. The BCHE gene variability seen in this survey differs from that of non-isolated populations in respect to both A539T and G390V allele frequency. The CHE2 C5+ phenotype frequency was 14.40% ± 2.22% and falls within the range of that found for other Brazilian Amerindian samples.